Stock investment knowledge, income and risk investment on investment decision making in Ambon City - Meiske Wenno; Muhammad Faisal (Institute of Computer Science (IOCS), 2023)
Knowledge of stock investment, income and risk investment is an important element to start investing. With basic knowledge about investment, it can trigger someone's interest to invest where this can be done as a consideration tool for making investment decisions. This study aims to determine 1). The effect of stock investment knowledge on investment decision making in Ambon City 2). The influence of income on investment decision making in Ambon City. 3) The influence of Risk Investment on the investment decision making of the people of Ambon City. The method used is quantitative research methods. The sample in this study was 102 investors. The data collection technique in this study used a questionnaire/questionnaire whose results had been tested. Based on the results of the study it can be concluded that 1). Stock investment knowledge has a significant effect on investment decision making seen from the results of regression analysis showing stock investment knowledge is 3.344 with a significance of 0.001 (significant). 2). Income has a significant effect on investment decision making as seen from the results of regression analysis showing income is 5,300 with a significance of 0.000 (significant). 3) Risk investment has a significant effect on investment decision making, as seen from the results of the regression analysis test showing that risk investment is 5.504 with a significance of 0.000 (significant).